(untitled) (Research, Society and Development, 2022)
Devices such as smartphones, tablets and e-book readers connect users to the world immediately, increasing information accessibility. Accordingly, mobile technologies to teach and learn has grown in education. In this context, many universities worldwide have started using smartphones to promote learning and disseminate information. In order to support technological resources for transmission of content, psychology through theories of learning investigates since last century possible contributions brought by machines into learning process. Based on gamified systems and Skinner’s radical behaviorism, using technological resources available, an educational software was developed on Android platform to access contents in the pharmacology field. The software was published on Google Play attaching a database with 310 questions and 810 images, as well as PDF files. Bringing gamified dynamics that involve drug’s questions and images, this application may be used, above all, to support traditional theoretical classes.